A Corpus-Based Study of Counterfactuals in Mandarin*. (October 2016) - Yong, Qian
This research aims to discover the working mechanisms for counterfactuals in Mandarin. Following statistical analyses, several key findings emerged. First, besides pragmatic influences, Mandarin counterfactuals are found to be positively correlated with negation, emphatic modals, optative mood, past-oriented temporality, first person pronoun, demonstratives, and so on. The strength of pragmatic influences is subject to the variation of features present in the sentences. Second, different hypothetical conjunctions work quite differently in their ability to generate counterfactuality. Third, some significant differences have been found both in the frequencies of counterfactuals and in marking strategies between Mandarin and English. My empirical findings were confirmed by a search through six corpora, namely the Lancaster Corpus of Mandarin Chinese, The University of California at Los Angeles (UCLA) Corpus of Written Chinese, Texts of Recent Chinese (TORCH), CLOB corpus (Brown family, British English), CROWN corpus (Brown family, American English) and The English–Chinese Bilingual Parallel Corpus.